Rapid maxillary expansion treatment increases mid-facial depth in early mixed dentition - Si, Jiaping; Hu, Xinyi; Du, Yu; Wei, Mengyao; Xu, Lehan; Li, Bing; Chen, Xiaoyan; Li, Xuan (Frontiers in Pediatrics, 2023)
Objective: To evaluate the effects of rapid maxillary expansion on mid-facial depth in early mixed dentition, and to delve into the relationship between mid-facial depth change and maxillary sinus and nasal cavity. Methods: 35 patients in mixed dentition treated with Haas expander were included in this study. All of the patients were scanned by CBCT before and after rapid maxillary expansion. Wilcoxon signed-rank test was performed to evaluate the changes in maxillary width, facial depth, maxillary sinus and nasal cavity volume between T0 and T1. Multiple linear regression analysis was applied to evaluate the correlations among them. Results: The hard and soft tissue facial depth in all measured planes showed significant increase (P < .001). The gain on the outer sagittal plane (1.04-1.52mm) was slightly more than that on the inner sagittal plane (0.91-1.30mm). Maxillary width and nasal cavity width increased 3.42±0.93mm (P < .001) and 2.25±0.77mm (P < .001) respectively after treatment. A gain was found in both nasal cavity volume (2236.15 mm3, P < .001) and maxillary sinus volume (1227.33 mm3, P < .001). Multiple linear regression analysis showed that with the increase of maxillary sinus volume, the facial depth increased as well (B=0.455-0.683, P < .05). And statistically significant correlations were found between nasal width and nasal cavity volume (B=0.384, P < .05). Conclusions: The depth of middle third face was significantly increase and the volume of maxillary sinus and nasal cavity was enlarged in early mixed-dentition patients who were undertaken by RME. The facial depth was related with maxillary sinus volume, and nasal cavity volume was related with nasal width.